PENGARUH PENAMBAHAN ENDOPOWER β® PADA RANSUM YANG MENGANDUNG BUNGKIL INTI SAWIT TERHADAP KARKAS DAN ORGAN DALAM AYAM BROILER - hasudungan silitonga (Jurnal Peternakan Integratif, 2015)
ABSTRACT This study aimed to determine the effect Endopower β® in diet of the carcass and visceral organs weight in broiler chickens. This research was conducted at the Laboratory Animal Sciences Program Husbandry Faculty of Agriculture, University of Sumatra Utara. The experiment was conducted for 35 days started from October to November 2013. The design experiment completely randomized design (CRD) with 5 treatments and 4 replications. This treatment consists of R0a (Diet Commercial 100%); Diet compose of 80% comercial diet and 20% palm kernel cake treated by level Endopower β® 0% (R0); 0,02%(R1); 0,04% (R2); 0,06%(R3). The result showed that addition endopower β® significantly (P<0,01) increased the average slaughter eight, carcass weight and carcass percentage. Level 0.06% of Endopower showed highest slaughter weghts, carcass weight and carcass percentage. It is concluded that endopower β® improve  slaughter weight, carcass weight, carcass percentage and decreased visceral organs weight. Keywords: Endopower β®, palm kernel cake, broiler chicken carcasses, visceral organs